The Effect of Service Quality on Visitors in Pentadio Resort Gorontalo Regency - Rifky Baruadi; Imam Mashudi; Maman Musa (LP2M Universitas Bina Mandiri Gorontalo, 2021)
This study aims to determine the effect of service quality on visitor interest at Pentadio Resort Gorontalo Regency. This research uses descriptive quantitative method. Respondents of this research are people who have ever enjoyed services at Pentadio Resort Gorontalo Regency with a total sample of 97 people. Data analysis using simple regression. The results showed that service quality had a positive and significant effect on visitor interest at Pentadio Resort, Gorontalo District